The construction of the HADES underground research laboratory and its role in the development of the Belgian concept of a deep geological repository - Li, Xiangling; Neerdael, Bernard; Raymaekers, Didier; Sillen, Xavier (Geological Society of London, 2024)
When the Belgian Nuclear Research Centre (SCK CEN) launched a research, development and demonstration programme on geological disposal in the 1970s, it was not certain if a deep geological repository could be constructed in poorly indurated clay. This was tested by constructing the HADES underground research laboratory (URL) in Boom Clay, 225 m below SCK CEN's site in Mol. The construction history of the URL reflects how the understanding of the Boom Clay increased and how the excavation techniques and design of the gallery lining improved. It demonstrated that shafts, galleries and crossings between galleries can be constructed using industrial techniques. It also allowed characterization of the hydromechanical response of the clay and the clay disturbances induced by the excavation. This increased understanding is also reflected in the evolution of the geological disposal concept considered in Belgium. The current disposal concept foresees the installation of seals in the shafts and galleries. The HADES URL also offered the opportunity to test possible seal designs and develop a better understanding of the behaviour of bentonite, a possible seal material, owing to its swelling capacity, under in situ conditions.